2021
DOI: 10.1101/2021.04.02.438237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex- and context-dependent effects of acute isolation on vocal and non-vocal social behaviors in mice

Abstract: Humans are extraordinarily social, and social isolation has profound effects on our behavior, ranging from increased social motivation following short periods of social isolation to increased anti-social behaviors following long-term social isolation. Mice are frequently used as a model to understand how social isolation impacts the brain and behavior. While the effects of chronic social isolation on mouse social behavior have been well studied, much less is known about how acute isolation impacts mouse social… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Finally, recent studies in rats and mice have shown that USVs of the opposite sex increase the sexual motivation of both male and female rats (Bialy et al, 2019; and mice (Pomerantz et al, 1983;Finton et al, 2017;Fernández-Vargas, 2018;Kuwaki and Kanno, 2021;Zhao et al, 2021). Sexual motivation in turn has been shown to be a strong reinforcer for mate choice (Matthews et al, 2005;Bialy et al, 2019).…”
Section: Ratsmentioning
confidence: 99%
“…Finally, recent studies in rats and mice have shown that USVs of the opposite sex increase the sexual motivation of both male and female rats (Bialy et al, 2019; and mice (Pomerantz et al, 1983;Finton et al, 2017;Fernández-Vargas, 2018;Kuwaki and Kanno, 2021;Zhao et al, 2021). Sexual motivation in turn has been shown to be a strong reinforcer for mate choice (Matthews et al, 2005;Bialy et al, 2019).…”
Section: Ratsmentioning
confidence: 99%
“…Aged (1-year-old) females emit less USVs compared to younger adult females (Moles et al, 2007). Furthermore, 3-days socially isolated females emit more USVs than group-housed females (Zhao et al, 2021).…”
Section: Female-female Interactionsmentioning
confidence: 98%
“…Male mice emit USVs during male-male social encounter, especially during sniffing the opponent male (K. Gillian D. Sales, 1972;Scattoni et al, 2011;Zhao et al, 2021), but not during aggressive encounter (Karigo et al, 2021;Gillian D. Sales, 1972;Whitney et al, 1973). The acoustic features of male-to-female and male-to-male USVs are similar, but the number of USVs during male-male encounter is smaller than male-female interactions (K. Zhao et al, 2021). The internal state behind USVs during male-male interactions are still not clear.…”
Section: Male-male Interactionsmentioning
confidence: 99%
“…However, mice predominantly emit USVs in social contexts with frequencies above 20 kHz. Mice USVs present many structurally and temporally complex acoustic features that can vary across developmental stage [ 10 , 90 , 105 , 156 ], genetic strains [ 157 , 158 ], gender [ 159 162 ], and social context [ 163 165 ] (Fig. 3 C).…”
Section: A Multidimensional Approach For Phenotyping Social Behaviormentioning
confidence: 99%
“…Although USV emission in mice is innate [ 176 ], it is highly influenced by social experience. For example, the acoustic features and syllable variables of male USVs to females are affected by the receptivity of the female (specifically, its estrous state) [ 169 ], the state of the female (i.e., vivid, anesthetized, or urine only) [ 164 ], female presence [ 169 ], and prior sexual [ 177 ] and social experience [ 161 , 165 , 178 ]. Male courtship USVs were found to be mediated by a distinct neural population in the PAG connected to downstream premotor vocal-respiratory neurons in the nucleus retroambiguus to control the temporal and spectral features of the emitted USVs [ 179 ].…”
Section: A Multidimensional Approach For Phenotyping Social Behaviormentioning
confidence: 99%